KARAKTER MORFOMETRIK DAN MORFOLOGI ABALON Haliotis squamata Reeve 1846 DI PESISIR SELATAN JAWA DAN BALI - Syamsul Bachry; Dedy Duryadi Solihin; Rudhy Gustiano; Kadarwan Soewardi; Nurlisa A. Butet (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2019)
The standard of measurement of abalone is very important because it can help to identify accurately abalone shellfish based on shell morphology. This research was aimed to examine the truss morphometric and morphologycal characters of Haliotis squamata intraspecies in the southern coastal Java and Bali. The research was conducted from December 2014 to August 2016. Abalone was collected based on the purposive sampling method, it was then identified. The shellfish of abalone was measured and analyzed by using principal component analysis (PCA), canonical discriminant analysis and cluster analysis. The results showed that PCA was able to separate Haliotis squamata populations from Java and Bali using combination of PCIII and PCIV based on the factor coefficient values. The key characters that separated Haliotis squamata from the population of Java and Bali were the combination of characters BF (0.535) for PCIII and characters CH (0.522) for PCIV. Canonical discriminant analysis showed that Bali was the highest sharing component value (100%) of intra population and also the lowest sharing component of inter population (0%). The highest percentage of similarity was 99.91% that indicated the population of Binuangeun and Pangandaran, while the lowest was 99.31% for the population of Banyuwangi and Bali. The morphological characteristics of Haliotis squamata species in several locations showed specific characters such as color patterns, textures and shapes.